Montagem de comunidades vegetais ao longo de um gradiente de severidade ambiental - Menezes, Bruno Sousa de (2015)
Community assembly processes can be explained from three perspectives: 1) classical (based on the duality between competition and abiotic filtering), 2) alternative (based on neutral processes), and 3) historical (based on evolutionary and biogeographical processes). Although studies on community assembly have been ongoing for four decades, there are still many conceptual issues surrounding the topic. We reviewed the main advances in these studies to provide an overview of assembly rules theory. We showed that: a) the published studies have improved their predictive aspect, usually associated with a well-consolidated test base; b) the hypothesis test by null models has been reinforced as a consistent data analysis method, being employed in several community organization studies; and c) the neutral theory has been an alternative to explaining coexistence by deterministic processes. In light of this, we also conducted a case study in the Brazilian semiarid region, intending to identify how different processes act in the assembly of plant communities along a severity gradient. It is known that the relative importance of these processes varies according to the environment. Abiotic filtering is generally stronger in more severe environments, while competition is more intense in milder environments (stress-dominance hypothesis). However, most studies that confirmed this tendency was carried out in gradients of conditions (e.g., temperature and fire). We hypothesize that under a resource gradient (e.g., water and soil nutrients), competition increases as abiotic filtering strengthens. We tested this hypothesis by analyzing the phylogenetic and functional structure (alpha and beta traits) of plant communities under different edapho-climatic factors. We found a phylogenetic signal in 91% of the analyzed traits. The phylogenetic and functional patterns ranged from clustered to random or dispersed as the environment became less stressful. We interpret these results as evidence of the joint action of abiotic filtering and competitive hierarchy in environments under any restriction of the resource (hydric or edaphic) and the greater importance of stochastic processes in favorable environments. We conclude that the assembly of communities on resource gradients is more complex than on gradients of conditions, which does not support the stress-dominance hypothesis and should be analyzed with as much evidence as possible.